The reorganization of global value chains: What's in it for Latin America and the Caribbean? - Mauricio Mesquita Moreira; Juan S. Blyde; Christian Volpe Martincus; Marcelo Dolabella; Ignacio Marra de Arti\~nano (Inter-American Development Bank (IDB), 2023)
As Latin America and the Caribbean bounce back from a sanitary crisis of historic proportions, the search is on for policies that can accelerate recovery while boosting longterm growth. In a scenario of tight fiscal constraints, trade and integration (T&I) policies seem to fit this description. There are particularly high expectations in some policy circles that the benefits of T&I policies will be boosted by an impending reorganization of global value chains. Yet, little is known about the relevance, shape and impacts of this reorganization: Will this lead to reshoring, nearshoring, or some slightly modified version of the status quo? Will this benefit the region? This paper takes a stab at helping to answer these questions. It begins with a critical review of the most frequently cited drivers of the reorganization. This is then followed by an analytical exercise that uses the 2018-2019 US import tariff hike as a quasi-natural experiment. The results seem more consistent with modest trade and investment gains for the region, associated with incremental rather than major adjustments in the global value chains. It concludes by arguing that, whatever the future brings, minimizing trade and investment costs is likely to remain the region's dominant strategy.
Keywords: 330; Value Chains; Trade; Latin America; Nearshoring